RUNNING EVENT “TRACKPRESSO: 5K COLOR RUN 2024 DI KOTA SEMARANG, JAWA TENGAH” - Regita Pratitis, Penthasuci; Manalu, S. Rouli (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2024)
This project discusses the preparation and execution of the Trackpresso: 5K Color Run 2024 event. Anak Panah Kopi, as the client, collaborated with the organizing team based on a desire to host a trending event in recent months, utilizing the